Features of the debt policy of the Russian Federation - S. V. Marchenko; V. V. Pogosyan; Zh. I. Golubina (Путеводитель предпринимателя)
The article describes the features of the debt policy of the Russian Federation, its objectives, assessed the current state of the public debt, determined by reason of its growth, it suggests ways to optimize the management of the external debt of the state.